Disbelief about the time. Timelessness in the late works of Paul Celan - Bartkuvienė, Inga (Literatūra, 2019)
The poetry of Paul Celan has a reflected intention to ask about the temporal determination of human being and simultaneously questions the term and definition of time. In may of his works he reflects he the catastrophic transformation, the reflection also includes the revision of the conventional conception of time. He tries to show, that beside the usual forms of historical, causal und linear time, individuals also perceive timelessness. Paradoxically, the accomplishment of a historical event (Holocaust) evokes a consciousness of the historical caesura, and thus of the untold and the inhospitable. In his perception, for the poet, writing (after holocaust) means writing after apocalyptic break, where history does not exist, in other words surrounded by the timelessness. The task of preserving the memory of what happened in poetry goes hand in hand with the awareness of a disorder and often borders on the impossibility of verbalizing what has happened or even being able to express itself verbally. The experience of disconnection from the temporal sequence of events (through trauma) coincides with the moments of speechlessness, emptiness in consciousness, verbal utterance, and time experience overlap. This tendency is radicalized especially in his late work. In this article late works of Paul Celan, that deal with the questions of timelessness and manifestations of it are analysed (“Zeitlücke”, “Die Trombonestelle” “Largo” and others).
Keywords: time; time layers; timelessness; subjectivity; verbalization of time-experience; problem of language; self-reflexion of literary work